Strategi Marketing Digital Rumah Batik Cipaku Bandung - Alfiannurdin, Nurlaila; Tresna, Pipin; Ruhidawati, Cucu (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This study aims to analyze the effectiveness of digital marketing strategies implemented by Batik Cipaku in increasing sales and maintaining its existence in a competitive market. In today's digital era, the development of internet technology has driven a shift in people's lifestyles and shopping habits from traditional (offline) to digital (online) methods. Batik Cipaku Bandung utilizes various social media platforms such as Facebook, Instagram, TikTok, and WhatsApp to reach consumers and promote its products. The results show that the digital marketing strategy applied by Batik Cipaku is effective in increasing the number of sales. Consumer trust increases because the products sold are in accordance with the specifications listed on social media and timely delivery of goods. Batik Cipaku also successfully combines online and offline marketing through physical stores, participation in arts and crafts exhibitions, and collaboration with local designers, further expanding its market reach. This study concludes that implementing the right digital marketing strategy can help batik companies like Batik Cipaku to remain competitive and relevant in the market. A marketing strategy that focuses on cultural values and product quality has proven effective in attracting consumer interest and positioning Batik Cipaku as one of the key players in Indonesia batik industry.